HUBUNGAN TINGKAT STRES IBU DAN PENGASUHAN PENERIMAANPENOLAKAN DENGAN KONSEP DIRI REMAJA PADA KELUARGA BERCERAI - Asilah, Asilah; Hastuti, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2014)
This study aimed to analyze relationship between level of maternal stress and parental acceptance-rejection with adolescent’s self-concept on divorced family. This cross-sectional study designed research were located at Tanah Sareal and Bogor Barat, Bogor city. This research involved 50 adolescents around age 12-18 from divorced family and their mothers were selected conveniencely. The data were collected by interview and selfreport using questionnaire. The level of maternal stress was measured by using symptoms of stress, parentingstyle measured by parental acceptance-rejection questionnaire (PARQ), while adolescents’s self concept was measured by adolescent self concept instrument. Result showed 80 percent of mothers had level of stress as mildcategorize. Level of maternal stress was negatively significant correlated with level of education, family monthly income, and family size, while positively significant correlated with length of divorce. Most of the adolescentsshowed higher percentage (98%) of acceptance from their mothers. Age of adolescents significantly correlated positively with aggression and undifferentiated rejection. A higher percentage of adolescents showed positive selfconcept (78%). The affection from mother was more strongly correlated positively with self-concept.